An Opioid-Sparing Strategy for Laparoscopic Sleeve Gastrectomy: A Retrospective Matched Case-Controlled Study in China - Yuanyuan Ma; Di Zhou; Yu Fan; Shengjin Ge (Frontiers Media S.A., 2022)
Background: Opioid-sparing anesthesia may enhance postoperative recovery by reducing opioid-related side effects. The present study was to evaluate the effect of an opioid-sparing strategy in bariatric surgery.Methods: This study was conducted as a retrospective matched case-controlled (1:1) study. A total of 44 patients receiving either an opioid-based approach (OBA group) or an opioid-sparing strategy (OSA group) who under laparoscopic sleeve gastrectomy were included between May 2017 and October 2020. The primary outcome was the postoperative hospital length of stay (PLOS). Secondary outcomes were the hospital costs, operative opioid consumption, time to recovery, postoperative pain score at rest and rescue antiemetic administered in the PACU.Results: The clinical demographic and operative data in both groups were comparable. There were no significant differences between the two groups in the PLOS (OSA vs. OBA: 6.18 ± 0.23 days vs. 6.73 ± 0.39 days, p = 0.24). Compared to the OBA group, opioid consumption in the OSA group was significantly decreased (48.79 ± 4.85 OMEs vs. 10.57 ± 0.77 OMEs, p < 0.001). There were no significant differences in the hospital costs, time to recovery, and rescue antiemetic administered, the incidence of intravenous opioids and vasopressor use in the PACU.Conclusion: The opioid-sparing anesthesia for laparoscopic sleeve gastrectomy was feasible but did not decrease the PLOS.